2014
DOI: 10.1016/j.neuron.2013.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ig/Caspr Recognition Promotes the Formation of Axoaxonic Synapses in Mouse Spinal Cord

Abstract: SummaryInhibitory microcircuits are wired with a precision that underlies their complex regulatory roles in neural information processing. In the spinal cord, one specialized class of GABAergic interneurons (GABApre) mediates presynaptic inhibitory control of sensory-motor synapses. The synaptic targeting of these GABAergic neurons exhibits an absolute dependence on proprioceptive sensory terminals, yet the molecular underpinnings of this specialized axoaxonic organization remain unclear. Here, we show that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 49 publications
2
64
0
1
Order By: Relevance
“…Such a possibility would be consistent with our results showing that PTPRG binds to CNTN3-6 in essentially identical fashion. These PTPRG⅐CNTN co-receptors might associate with known CNTN-binding partners, such as L1 family members, CNTNAPs, or amyloid precursor proteins (8,11,32,34,35). Targets of PTPRG⅐CNTN co-receptor complexes might also include yet to be identified proteins that have weak affinities for either PTPRG or a given CNTN but would associate with a PTPRG⅐CNTN co-receptor complex to form a holoreceptor in much the same way that semaphorins, neuropilins, and plexins do (36).…”
Section: Discussionmentioning
confidence: 99%
“…Such a possibility would be consistent with our results showing that PTPRG binds to CNTN3-6 in essentially identical fashion. These PTPRG⅐CNTN co-receptors might associate with known CNTN-binding partners, such as L1 family members, CNTNAPs, or amyloid precursor proteins (8,11,32,34,35). Targets of PTPRG⅐CNTN co-receptor complexes might also include yet to be identified proteins that have weak affinities for either PTPRG or a given CNTN but would associate with a PTPRG⅐CNTN co-receptor complex to form a holoreceptor in much the same way that semaphorins, neuropilins, and plexins do (36).…”
Section: Discussionmentioning
confidence: 99%
“…The calyceal synapses of vestibular hair cells in the mouse show a high similarity to septate junctions in EM microscopy and contain both Caspr and contactin, with loss of Caspr resulting in the separation of the membranes at the synapse (Lysakowski et al, 2011;Sousa et al, 2009). Recently, it has been demonstrated that a contactin5 (CNTN5)-Caspr4 complex together with the IgCAM NgCAM-related cell adhesion molecule (NrCAM) guides the formation of synapse-to-synapse (axoaxonic) synapses between GABAergic interneurons and sensory motor synapses in the spinal cord, and there are likely to be other examples of 'transitional' synapses that would benefit from further molecular characterization (Ashrafi et al, 2014).…”
Section: The Septate Junction and Its Originsmentioning
confidence: 99%
“…Характерной чертой контактинов является большой размер -порядка 1.2 M bp в случае Cntn5. Всего описано шесть схожих по структуре генов контактинов, которые экспрессируются в основном в нейронах головного (Kleijer et al, 2015) и спинного мозга (Ashrafi et al, 2014) и регулируют образование синапсов между нейронами, обеспечивая различные аспекты нерв-ной деятельности. Контактин-5 экспрессируется главным образом в центральной нервной системе (Ogawa et al, 1996), а его максимальная экспрессия обнаруживается у эмбрионов мышей начиная с 16-го дня и на 2-й день после рождения (Li et al, 2003).…”
unclassified